Bioactive Secondary Metabolites from an Arctic Marine-Derived Strain, Streptomyces sp. MNP-1, Using the OSMAC Strategy - Mengna Wu; Zijun Liu; Jiahui Wang; Wentao Hu; Huawei Zhang (Molecules, 2025)
An Arctic marine-derived strain, MNP-1, was characterized by a combined methodological approach, incorporating a variety of analytical techniques including morphological features, biochemical characteristics, and 16S ribosomal RNA (rRNA) sequence analysis. The chemical investigation of Streptomyces sp. MNP-1 using the OSMAC (one strain many compounds) strategy yielded the isolation of twenty known compounds (1–20), which were unambiguously identified by various spectroscopic approaches including 1H and 13C NMR and ESI-MS (previously reported data). Bioassay results indicated that compounds 2, 3, 5, 9, 14, 15, and 20 had antimicrobial activity against human pathogenic strains including Staphylococcus aureus, Escherichia coli, and Candidaalbicans with MIC values ranging from 4 to 32 μg/mL, and compounds 3 and 14 exhibited moderate inhibitory activity on A549, MCF-7, and HepG2 tumor lines showing IC50 values within the range of 19.88 to 35.82 µM. These findings suggest that Streptomyces sp. MNP-1 is one of the prolific manufacturers of bioactive secondary metabolites with therapeutic potential.